A high-performance SDC-infiltrated nanoporous silver cathode with superior thermal stability for low temperature solid oxide fuel cells - Lee, Tsung-Han (2020)
Superior thermal stability of a nanoporous silver thin film cathode is enabled by covering the silver nanoparticles with a thin layer of samarium-doped ceria (SDC). A simple solution infiltration process followed by post heat treatment at 500 °C is applied to coat a thin SDC layer over inkjet-printed silver nanoparticle thin films to physically confine the silver nanoparticles to prevent thermal agglomeration. The electrochemical performance of the SDC-infiltrated silver cathode also surpasses that of both a non-infiltrated silver cathode and a typical sputtered nanoporous platinum cathode. A 60 hour fuel cell current stability test using the SDC-infiltrated silver cathode shows only 12.4% current degradation, which is significantly lower than 73.6% degradation from the fuel cell using a non-infiltrated silver cathode.